2014
DOI: 10.35808/ijeba/39
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Effective Human Resource Management Practices on Job Satisfaction: The Case of National Bank of Greece

Abstract: An organization's success in today's competitive business environment is mainly based on human capital and banking institutions andthere is no exception to this. Satisfied and loyal employees are the most important assets of an organization, and primarily responsible for productivity and profitability. This study examines the level of employee satisfaction in the National Bank of Greece and attempts to identify the contributing factors. The survey covered 366 employees in Greek branches of the National Bank of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Most employees prefer to work in a more friendly environment, have mutual trust and dominant informal relationships among co-workers, consider personal ambitions, and value teamwork. [12] Coworkers have the biggest influence on employee job satisfaction (Dimitriadis et al, 2014). The study show that the remuneration influence on job satisfaction is the most significant.…”
Section: Literature Reviewmentioning
confidence: 81%
See 1 more Smart Citation
“…Most employees prefer to work in a more friendly environment, have mutual trust and dominant informal relationships among co-workers, consider personal ambitions, and value teamwork. [12] Coworkers have the biggest influence on employee job satisfaction (Dimitriadis et al, 2014). The study show that the remuneration influence on job satisfaction is the most significant.…”
Section: Literature Reviewmentioning
confidence: 81%
“…A positive influence was also found on employee job satisfaction on operational factors, such as job security, skill utilization, and the ability and character of the job. [13] Murrells et al (2008) who used nurses at the beginning of their careers showed that time utilization on employee job satisfaction at the beginning of a career is highly dependent on the existing job, even for the same profession. Nurses dealing with child, and mental health work under different conditions, with different organizational cultures leading to different experiences.…”
Section: Literature Reviewmentioning
confidence: 99%